Mergers in India: exploiting financial synergies - "Kaur, Paramjeet" (New Delhi, 2012)
In view of the restructuring of the Indian corporate sector, this book carries out an in-depth analysis of the mergers and acquisitions that took place in India's pharmaceutical industry since the early 1990s. Using innovative methodology, this record answers two important questions: "Why is a firm acquired?" and "Why does a firm acquire?" As it examines how acquired firms differ from the acquiring--and how participant firms are different from the nonparticipants--it argues that corporate amalgamation has important efficiency and policy implications. This record also includes an appraisal of industrial and stock market reforms, where the concern over the need for a "takeover market in India" is developed.
Keywords: Consolidation and merger of corporations-India